The Depiction of Trauma and its Effect on Character Development in the Brontë Fiction. (1st April 2013) - Morris, Patrick
<x xml:space="preserve">Abstract</x> The novels written by the Brontë sisters remain popular today and as authors they are highly regarded for their ability to express powerful emotions in their characters. This article analyses the portrayal of trauma in the form of child abuse and domestic violence in three key texts: Jane Eyre by Charlotte Brontë, Wuthering Heights by Emily Brontë and The Tenant of Wildfell Hall by Anne Brontë. The authors' intuitive understanding of trauma, both in its realistic depiction and its effect on character development is detailed with reference to modern psychological insights and recent literature on the psychological impact of trauma.